Pelatihan Event Manajemen Dalam Meningkatkan Komunikasi Internal Karang Taruna Dusun Sadawarna Subang - Nuraeni, Nuraeni; Nurhadi, Zikri Fachrul; Khoerunisa, Dhina; Yasmin, Nada Kamelya (Jurnal Media Pengabdian Komunikasi, 2024)
Abstract Effective internal communication plays a crucial role in the successful execution of events within an organization. This research aims to socialize event management to enhance the intensity of internal communication within Karang Taruna of Dusun 1 Sadawarna, Sadawarna Village, Cibogo District, Subang Regency. Based on observations, the intensity of internal communication within the organization has not been optimal, which has resulted in a lack of coordination and participation among members when organizing activities. To address this issue, a socialization program was conducted through training, involving 15 participants from the Karang Taruna members. The training included presentations, as well as pre-test and posttest assessments to measure changes in understanding of event management. The results showed an 11% improvement in understanding event management, with the average pre-test score increasing from 55.33 to 66.33 in the post-test. In conclusion, this training positively contributed to improving the quality of event execution in Dusun 1 Sadawarna, while also providing additional insights and practical guidance for Karang Taruna and village officials in managing events more systematically and effectively. Keywords: Event management; communication management; organizational communication. Abstrak Komunikasi internal yang efektif memainkan peran penting dalam keberhasilan pelaksanaan event dalam sebuah organisasi. Artikel ini bertujuan untuk mensosialisasikan event management dalam meningkatkan intensitas komunikasi internal di Karang Taruna Dusun 1 Sadawarna, Desa Sadawarna, Kecamatan Cibogo, Kabupaten Subang. Berdasarkan observasi intensitas komunikasi internal di organisasi tersebut belum optimal, yang berdampak pada kurangnya koordinasi dan partisipasi anggota saat melaksanakan kegiatan. Untuk mengatasi masalah ini, dilakukan sosialisasi dengan metode pelatihan yang melibatkan 15 peserta dari anggota Karang Taruna. Pelatihan meliputi pemaparan materi, serta pre-test dan post-test untuk mengukur perubahan pemahaman mengenai event management. Hasil pengabdianm ini menunjukkan peningkatan pemahaman tentang manajemen acara sebesar 11%, dari nilai rata-rata pre-test 55,33 menjadi 66,33 pada post-test. Kesimpulannya, pelatihan ini berkontribusi positif terhadap peningkatan kualitas pelaksanaan kegiatan di Dusun 1 Sadawarna serta memberikan wawasan tambahan dan gambaran nyata bagi Karang Taruna serta aparatur desa dalam mengelola event secara lebih terstruktur dan efektif. Kata-kata kunci: Event manajemen; manajemen komunikasi, komunikasi organisasi.